2014
DOI: 10.1002/pi.4775
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and characterization of compatibilized poly(lactic acid)-based blends and their nanocomposites with silver-loaded kaolinite

Abstract: Kaolinite layers were made apart by silver particle intercalation through chemical reduction. The modified clay then allowed formation of intercalated‐exfoliated composites based on poly(lactic acid) with properties notably enhanced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 32 publications
(67 reference statements)
3
27
0
Order By: Relevance
“…dimethyl sulfoxide (DMSO) [9]. Moreover, the addition of metal nanoparticles such as silver (Ag) into the interlamellar space of KT, during reduction reactions by DMSO, can help to increase interlamellar space of KT [5,10,11], leading to higher clay dispersion in polymer matrix. The presence of Ag nanoparticledeposited KT not only enhances gas barrier properties by action of the clay layers, but also inhibits bacterial growth on polymer film by function of Ag nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…dimethyl sulfoxide (DMSO) [9]. Moreover, the addition of metal nanoparticles such as silver (Ag) into the interlamellar space of KT, during reduction reactions by DMSO, can help to increase interlamellar space of KT [5,10,11], leading to higher clay dispersion in polymer matrix. The presence of Ag nanoparticledeposited KT not only enhances gas barrier properties by action of the clay layers, but also inhibits bacterial growth on polymer film by function of Ag nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, there have been several studies regarding KT as a filler for polymer matrices, particularly ethylene-vinyl alcohol (EVOH) copolymers [12], poly(m-xylene adipamide) (MXD6) resin [8], polylactide [13], cassava starch [14,15], polyolefin/iron [16], polyimide [17] and poly(lactic acid)/poly(butylene adipateco-terephthalate) (PLA/PBAT) [5]. The authors consistently reported that KT-polymer nanocomposites exhibited a significant improvement in tensile strength, elongation at break, thermal resistance, UV blocking, and dramatically better waterproofing, including water vapour and gas barrier properties [5,8,12e17].…”
Section: Introductionmentioning
confidence: 99%
“…PBS [grade GS-Pla AZ91TN: Mn = 57,200 gmol -1 , PDI = 3.0, melt flow rate = 4.5 g (10 min -1 )] was purchased from Mitsubishi Chemical Corporation (Toyoto, Japan) and polycaprolactone (PCL 440744) with Mn 80,000 gmol -1 and Mw/Mn \ 2 was purchased from SigmaAldrich (Brunei, Singapore). PLA film (thickness & 50 lm) was prepared via the blown film technique at the Department of Chemistry, Faculty of Science, Chiang Mai University (Girdthep et al 2015). T4 DNA ligase and DNA polymerase were purchased from Promega (Madison, WI, USA).…”
Section: Chemicals and Materialsmentioning
confidence: 99%
“…Then, soaked the bones in oxidizing solution for 72 h and calcined at 950 °C for 12 h [8]. Finally, milling and sieving to be powders [6].…”
Section: Preparation Of Hydroxyapatite (Ha)mentioning
confidence: 99%
“…butoxide 0.01% mol per 500 g lactic acid to PLA powders (Molecular weight = 100,000-150,000 and viscosity = 2.17 ± 0.059 cP) [6,8,9].…”
Section: Preparation Of Poly-l-lactic Acid (Pla)mentioning
confidence: 99%